2012
DOI: 10.1100/2012/842301
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Regulates Proliferation and Apoptosis in Human Prostate

Abstract: This paper aimed to evaluate the leptin role on the cellular proliferation and the expression of fibroblast growth factor 2, aromatase enzyme, and apoptotic genes in the human prostate tissue. Methods. Fifteen samples of hyperplasic prostate tissue were divided in four symmetric parts maintained in RPMI medium supplemented with 10% fetal bovine serum, 1 ng/mL of gentamicin, and added with 50 ng/mL leptin (L) or not (C). After 3 hours of incubation, gene expression was evaluated by real time RT-PCR. Cellular pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…6 and 3 (4/5) [22]. Moreover, Leze et al demonstrated that incubation of human hyperplastic prostate tissue fragments with LEP (50 ng/mL) for 3 h significantly stimulates proliferation of epithelial cells and expression of pro-apoptotic BAX gene [23].…”
Section: Introductionmentioning
confidence: 99%
“…6 and 3 (4/5) [22]. Moreover, Leze et al demonstrated that incubation of human hyperplastic prostate tissue fragments with LEP (50 ng/mL) for 3 h significantly stimulates proliferation of epithelial cells and expression of pro-apoptotic BAX gene [23].…”
Section: Introductionmentioning
confidence: 99%
“…Leptin receptor (ObR) may activate genes responsible for cell proliferation and angiogenic factors such as VEGF [ 30 , 31 ]. Leptin is expressed and synthesized by prostate and is involved in normal physiological growth of prostate gland [ 32 ]. Overexpression of leptin may result in extensive proliferation and, ultimately, prostate hyperplasia or cancer [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are a few reports that leptin is associated with proliferation of the prostate; Leptin seems to have an important role in maintaining the physiological growth of the prostate. In hyperplasic prostate tissue, leptin treatment increased cellular proliferation and decreased apoptosis [ 47 ]. It is also reported to stimulate the proliferation of a BPH-1 cell and a prostate cancer cell line (PC-3 cell) via estrogen metabolism [ 48 ].…”
Section: Discussionmentioning
confidence: 99%